I want to publish but ...: Barriers to publishing for women at a University of Technology - A. Garnett; F. E. Mahomed (Perspectives in Education, 2012)
This article documents the experiences of a community of practice (CoP) of female academics with regard to the notion of publishing. The non-probability, purposive sample utilised in the study, comprised a group of female academics who were involved in a women in research programme at a University of Technology (UoT). The purpose of the article was to explore the personal and professional barriers the women may have experienced with regard to academic publishing. A qualitative paradigm was used, by means of a case study approach. It was expected that the data might indicate a specific gendered overload for the sample group with regard to publishing, as well as produce anomalous outcomes as a result of the UoT setting. However, women were not found  to be specifically conscious of their gendering, but rather experienced barriers to publishing mainly as a result of high administrative workloads in the institution. The article adds to the body of knowledge in that it (1) maintains that the main barrier to publishing in this case is not compounded by gender. (2) Shows that workload pressure is similar in a University of Technology environment as in a traditional university environment, and (3) documents the experiences of a CoP and the success thereof, which could be duplicated in other environments.